N-alkanes Sources and Distribution in the Sediment of Khor-Al Zubair Southern Iraq - Abo-Turab, Fatima F.; Mohammed, Abbas H.; Al-saad, Hamid T. (Mesopotamian Journal of Marine Sciences, 2025)
In this study, sediment samples from five stations were collected, aliphatic compounds were extracted, and the samples were analyzed by using a gas chromatograph in order to determine the pollution levels caused by normal alkanes concentrations in the Khor Al-Zubair in Basrah. The highest concentration was 10.10965 ng/g in the fifth station, while the lowest concentration was 0.91264 ng/g in the third station. The results showed that anthropogenic was the dominant origin,where Carbon Preference Index (CPI) ranged from 0.7181 in the third station to 1.0592 in the fifth station, and Pristine/Phytane ranged from 0.316547 in first station to about 0.730581 in second station. The C17/Pristine ratio shows that the most common origin is the anthropogenic where it ranged between 0.773271 in the third station and 1.905842 in the fourth station, and C18/Phytane ranged from 0.974346 in the fourth station to about 2.770045 in the first station. The concentrations of total organic carbon (TOC) were determined in sediment samples. The highest concentration was 0.193 in the second station and the lowest concentration was 0.076 in the first station. According to our knowledge this study is the first to determine the n-alkane in Khor Al-Zubair region.